The Effect Of Giving Cucumber Juice On Reducing Blood Pressure In Hypertension Patients At Imelda Pekerja Indonesia General Hospital 2023 - Noradina Noradina; Meriani HS; Bernita Silalahi; Paskah rina Situmorang; Deddy Sepadha Sagala; Desmawati Ndruru (International Journal Of Health Science, 2023)
Hypertension or high blood pressure is the main cause of heart system disorders, because known as the number one killer in the world, called the silent killer silently) because people with high blood pressure often do not show symptoms . The aim of this research was to determine the effect of giving cucumber juice on lowering blood pressure hypertension sufferers. This type of research is Quantitative research uses a quasi-experimental design with this type of design One group pre-post test was used. The study population was 33 hypertensive patients. The sample research formula uses the Slovin formula so that the research sample is 30 0 people. By giving cucumber juice once a day in the morning before breakfast 15-30 minutes 250 ml for 7 consecutive days. And analyzed univariately and bivariately using a paired sample t-test (between before and after intervention). Research result showed that blood pressure values were obtained after the intervention was carried out decrease and seen from the p value of 0.000 <0.05 it can be concluded that there is an influence from giving cucumber juice to reducing blood pressure in hypertensive patients .